Primary prevention of atrial fibrillation in patients with metabolic syndrome: correction of modifiable risk factors - A. I. Olesin; I. V. Konstantinova (Фундаментальная и клиническая медицина)
Currently, around 34 million people worldwide suffer from atrial fibrillation (AF), with the number projected to double by 2060. Despite the treatment of AF has been significantly improved during the recent years, AF is still associated with an increased risk of severe complications such as systemic thromboembolism, progression of heart failure, stroke, and myocardial infarction. Due to a high risk of disability and mortality, AF represent a major socioeconomic problem for the healthcare in most countries, also because of related financial costs. Obesity, most often represented by metabolic syndrome, is widely recognized as an epidemic of the XXI century. Here we review the features of AF development in patients with metabolic syndrome, suggesting novel avenues for the primary prevention of AF.